Whole issue - Language Value (Universitat Jaume I. Department of English Studies, 2020)
Table of Contents Articles  An investigation of scaffolding strategies to support structured inquiry language teaching to novice learners in a Primary school setting Amelie Langdon Jillian Pandor English in the Linguistic Landscape of Thailand: A Case Study of Public Signs in Hat Yai Ana Cristina Vivas-Peraza Audiovisual translation tools for the assessment of hard of hearing students Ana María Hornero Corisco Pilar González-Vera Learning vocabulary for IELTS Academic Reading: An evaluation of some pedagogical materials Marta Serrano Book Reviews  Patricia Bou-Franch and Pilar Garcés-Conejos Blitvich Analyzing Digital Discourse: New Insights and Directions Reviewed by Daniel Pascual Joss Moorkens, Sheila Castilho, Federico Gaspari and Stephen Doherty Translation Quality Assessment: From Principles to Practice Reviewed by Rocío Caro Quintana Anna Matamala Accessibilitat i traducció visual Reviewed by Ana-Isabel Martínez-Hernández